Faster Hypothermia Induced by Esophageal Cooling Improves Early Markers of Cardiac and Neurological Injury After Cardiac Arrest in Swine. Issue 21 (6th November 2018) - Xu, Jiefeng; Jin, Xiaohong; Chen, Qijiang; Wu, Chunshuang; Li, Zilong; Zhou, Guangju; Xu, Yongan; Qian, Anyu; Li, Yulin; Zhang, Mao
Abstract : Background: After cardiopulmonary resuscitation, the protective effects of therapeutic hypothermia induced by conventional cooling are limited. Recently, esophageal cooling (EC) has been shown to be an effective, easily performed approach to induce therapeutic hypothermia. In this study we investigated the efficacy of EC and its effects on early markers of postresuscitation cardiac and neurological injury in a porcine model of cardiac arrest. Methods and Results: Thirty‐two male domestic swine were randomized into 4 groups: sham control, normothermia, surface cooling, and EC. Sham animals underwent the surgical preparation only. Ventricular fibrillation was induced and untreated for 8 minutes while defibrillation was attempted after 5 minutes of cardiopulmonary resuscitation. At 5 minutes after resuscitation, therapeutic hypothermia was induced by either EC or surface cooling to reach a target temperature of 33°C until 24 hours postresuscitation, followed by a rewarming rate of 1°C/h for 5 hours. The temperature was normally maintained in the control and normothermia groups. After resuscitation, a significantly faster decrease in blood temperature was observed in the EC group than in the surface cooling group (2.8±0.7°C/h versus 1.5±0.4°C/h; P <0.05). During the maintenance and rewarming phases the temperature was maintained at an even level between the 2 groups. Postresuscitation cardiac and neurological damage was significantly improved in the 2 hypothermic groups compared with the normothermia group; however, the protective effects were significantly greater in the EC group. Conclusions: In a porcine model of cardiac arrest, faster hypothermia successfully induced by EC was significantly better than conventional cooling in improving early markers of postresuscitation cardiac and neurological injury.